2020
DOI: 10.1139/apnm-2019-0378
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged treadmill running in normobaric hypoxia causes gastrointestinal barrier permeability and elevates circulating levels of pro- and anti-inflammatory cytokines

Abstract: This study examined the impact of treadmill running in normobaric hypoxia on gastrointestinal barrier permeability and the systemic inflammatory response. Ten recreationally active participants completed two 1-h bouts of matched-workload treadmill exercise (65% normoxic maximal oxygen consumption) in counterbalanced order. One bout was performed in normoxia (NORM: fraction of inspired oxygen (FIO2) = 20.9%) and the other in normobaric hypoxia (HYP: FIO2 = 13.5%). Minute ventilation, respiratory rate (RR), tida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 57 publications
8
22
1
Order By: Relevance
“…* P ≤ 0.05. n = 9. Similar to our findings, Lee and Thake (2017) and Hill et al (2020) reported increases in I-FABP following exercise in hypoxic (13.5%…”
Section: Discussionsupporting
confidence: 93%
“…* P ≤ 0.05. n = 9. Similar to our findings, Lee and Thake (2017) and Hill et al (2020) reported increases in I-FABP following exercise in hypoxic (13.5%…”
Section: Discussionsupporting
confidence: 93%
“…Finally, we were not able to set another trial using the same absolute exercise intensity between hypoxia and normoxia. In the previous study, endurance exercise under hypoxia caused greater IL-6 elevation compared with exercise at the same absolute exercise intensity (i.e., same running velocity) under normoxia (Hill et al, 2020). Therefore, muscle damage and inflammatory responses after endurance training hypoxia may be augmented when the same absolute exercise intensity is selected under normoxia.…”
Section: Discussionmentioning
confidence: 85%
“…Some of the previous studies demonstrated the effect of a single session of exercise under hypoxia on muscle damage and inflammatory response (Sumi et al, 2018;Britto et al, 2020;Hill et al, 2020). In our previous study, we compared the acute responses of muscle damage and inflammation following a single session of endurance exercise between hypoxia and normoxia.…”
Section: Introductionmentioning
confidence: 97%
“…Where measured, I-FABP responses quickly recover within 1-2 h of exercise termination, irrespective of the intensity/duration of the protocol [124,140]. Like DSAT results, I-FABP responses are elevated in otherwise matched exercise interventions comparing: hypoxic (F i O 2 = 0.14) versus normoxic environments [137,143]; permissive dehydration versus rehydration [144]; and post NSAID ingestion [123]. In comparison, since initial investigation [86], no studies have monitored the magnitude and time-course of I-BABP responses following exercise.…”
Section: Severity Of Gi Barrier Integrity Loss Following Exertional-hmentioning
confidence: 90%